Fadiga de ligas de titânio com superfície modificada com nanotubos - Bortolan, Carolina Catanio (2016)
Among the surface modification techniques to improve the fixation, biocompatibility and corrosion resistance of titanium implants, one of the most recent and promising is the electrochemical anodization in electrolytes with fluoride ions. This technique results in the formation of highly ordered arrays of titanium oxide nanotubes on the surface of these materials. Many researchers evaluated the biological performance of these arrays and obtained satisfactory results, showing that the formation of hydroxyapatite and cellular development are higher after its formation. However, there are no records about the study of fatigue behavior of titanium alloys after this surface treatment; an essential evaluation since the surface conditions of the implants influence the fatigue properties, especially crack nucleation, and the orthopedic implants are subjected to cyclic loads when in service. In this context, the objective of this research was to evaluate the effect of the formation of TiO2 nanotubes, through electrochemical anodization technique in a solution containing fluoride ions, on the fatigue performance of Ti-6Al-4V and Ti-6Al-7Nb alloys, using the staircase method to develop fatigue tests and taking the polished surface condition as reference. SEM, AFM and XRD techniques were applied to characterize the surfaces and to support the fatigue results. The fatigue limit for 5 million cycles, calculated by the statistical method of Dixon-Mood, was maintained for the Ti-6Al-4V alloy (846MPa ± 13 MPa) after the formation of nanotubes on its surface and presented an insignificant reduction in statistical terms for the Ti-6Al-7Nb alloy (846 MPa ± 13 MPa for the polished surface condition and 825MPa ± 11 MPa for the modified surface). The maintenance of fatigue properties of the alloys after electrochemical anodization was mainly attributed to the small scale of the average lengths of the nanotubes and to the existence of a compact oxide layer in contact with the metal substrate (corresponding to the completely closed bottom of nanotubes).